Fire and landscape context shape plant and butterfly diversity in a South African shrubland. (5th April 2021) - Topp, Emmeline N.; Tscharntke, Teja; Loos, Jacqueline
Abstract: Aim: To understand effects of fire history and landscape composition on butterfly diversity in a fragmented agricultural landscape. Location: We studied critically endangered renosterveld remnants within the fynbos biome in the Swartland municipality, Western Cape, South Africa, a global biodiversity hotspot. Method: We selected survey sites on renosterveld fragments in the agricultural landscape along a gradient of fire history to test the response of biodiversity patterns to fire and landscape composition. We surveyed butterfly species richness, abundance and community composition as well as vegetation structure in five survey rounds on 58 sites between August 2018 and April 2019. We analysed data through linear modelling and multidimensional scaling. Results: Fire was associated with reduced shrub and understorey plant cover and with increased plant species richness. Butterfly species richness was three to four times higher when natural habitat increased in the surrounding landscape (within a 2 km radius), while butterfly abundance was negatively associated with increasing time since fire, with approximately 50% fewer individuals after 9 years. Fire was indirectly associated with increased butterfly species richness and abundance through the alteration of vegetation structure, particularly through removal of shrubs and enhanced plant diversity. Low‐mobility butterfly species were more positively associated with less vegetation cover than were high‐mobility species, which were more associated with sites characterized by long absence of fire. Main conclusions: Our findings suggest that species respond differently to fire, so a diversity of fire frequencies is recommended. Partially burning areas approximately every 10 years may benefit particularly low‐mobility butterfly species through gap creation and fostering plant diversity. Hence, including fire into management activities can benefit butterfly and plant populations alike in critically endangered renosterveld.